Margareth Truman “Murder Inside the Beltway” Novel: The Structure and Construction of Identity - Jubilezer Sihite; Rony Arahta Sembiring; Sabam Simandalahi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This article examines multicultural literature as a significant and strategic object of study in responding to problems. Multicultural literature is focused on multicultural issues that are often found in literary works. The main issues are related to certain identities or characteristics. This article examines the structure and identity construction of the murderous character in the novel Beltway (capital crime #24) by Margaret Truman, with the main focus on identity issues: (1) identity and identity issues; (2) articulation of identity; (3) text representation of identity discourse in the novel. The sociology of literature approach is used to understand reality in multicultural literary texts, especially in novels and their relation to the phenomenon of identity issues in other fields of study. The results of the study show that the process of identity articulation and text representation in identity discourse in multicultural social phenomena as well as identity issues and the process of identity articulation in multicultural societies deserve more serious attention. An identity is not stable but dynamic in the face of development.